Financial services - Mohan, S. (ed.); Elangovan, R. (ed.) (New Delhi, 2008)
The process of economic reforms gained momentum due to far-reaching changes in the economy in general and the financial system in particular. Financial markets have been increasingly influenced in recent times by financial innovations in terms of products and instruments, adoption of modern technologies, liberalization, opening up of the market to the global economy, streamlining of the regulatory framework and so on. Similarly, many innovative financial products are introduced to cater to the varied requirements of both corporate and individual customers. Despite the commendable progress in the financial system, several weaknesses too have developed, particularly in the banking sector, due to, inter alia, its rapid expansion, organizational deficiencies and inadequate technology. The growth of the financial system is, indeed, vital to the process of economic development as it helps to mobilize savings and channelise them in the various sectors of the economy for the purpose of growth and development. This book deals with the various aspects of financial services in 31 chapters authored by leading professors of different universities and colleges. Comprehensiveness, analytical approach and clarity are the salient features of the book. It is sure to serve as a good text material for the students. It will also be of interest and use to research scholars, teachers and policy makers.
Keywords: Financial service-India